Self-leadership and psychological capital as key cognitive resources for shaping health-protective behaviors during the COVID-19 pandemic - Sherry A. Maykrantz; Luke A. Langlinais; Jeffery D. Houghton; Christopher P. Neck (Administrative Sciences, 2021)
As COVID-19 has become a global pandemic, health researchers and practitioners have focused attention on identifying the factors that may help to shape health-protective behaviors, protecting individual health and well-being, and helping to mitigate the spread of COVID-19. This study explores the potential role of self-leadership and psychological capital (PsyCap) as key cognitive resources for shaping health-protective behaviors. Using multiple theoretical frameworks (social cognitive theory, psychological resources theory, and the health belief model), this paper develops and tests a hypothesized serial mediation model in which PsyCap and coping self-efficacy mediate the relationship between self-leadership and health-protective behaviors including hand washing, wearing face masks, and social distancing. Results suggest that PsyCap and coping self-efficacy mediate the positive relationship between self-leadership and health-protective behaviors. These results yield valuable insights regarding the usefulness of self-leadership and PsyCap as cognitive resources for shaping health-protective behaviors and for possible self-leadership and PsyCap interventions, potentially tailored to at-risk populations, which should have practical benefits for both the current and future pandemics and health crises.
Keywords: 350; coping self-efficacy; COVID-19; health protective behaviors; psychological capital (PsyCap); self-leadership